Method of piling and pilecap works on reclamation land / Nur Hakimah Fazil - Fazil, Nur Hakimah (Universiti Teknologi MARA UiTM,Perak, 2022)
This report is about the method of piling and pile cap works on reclamation land especially for high rise building. The aim for this is to know the method of piling works. Other than that is to learn the effectiveness to build high rise building on reclamation land. Main objectives for this report is to know the solution for pile that have issue and method of piling and pile cap. Pile Driving Analyzer (PDA) Restrike is one of the method of testing the pile. In conclusion, get to gain new knowledge about the foundation works on the reclamation land.